2007
DOI: 10.1177/0310057x0703500518
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan in Acute Pulmonary Embolism

Abstract: He had a past history of deep venous thrombosis and and thrombolysis 1 , alteplase was withheld due to a was therefore added in the belief it would help stabilise the patient. The levosimendan infusion Within four hours of the levosimendan infusion a O 2 to FiO 2 ratios. The patient was independent of non-invasive ventilatory and vasopressor therapy within 36 hours and DISCUSSION It has been reported that 10 to 15% of patients with 2 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…reported a case with a 72 year old man suffering from life-threating acute pulmonary embolism. 52 Due to a history of upper gastrointestinal bleeding and a poor pre-morbid status, medical, invasive, and surgical treatments were unfavorable. The patient received a 24 h levosimendan infusion that, after transient hypotension and tachycardia, improved the patient with hemodynamic stabilization, increasing P a O 2 , and improvement in metabolic parameters.…”
Section: Levosimendan In Phmentioning
confidence: 99%
See 1 more Smart Citation
“…reported a case with a 72 year old man suffering from life-threating acute pulmonary embolism. 52 Due to a history of upper gastrointestinal bleeding and a poor pre-morbid status, medical, invasive, and surgical treatments were unfavorable. The patient received a 24 h levosimendan infusion that, after transient hypotension and tachycardia, improved the patient with hemodynamic stabilization, increasing P a O 2 , and improvement in metabolic parameters.…”
Section: Levosimendan In Phmentioning
confidence: 99%
“…In acute and chronic pulmonary thromboembolism, only two case reports have been published. Powell et al reported a case with a 72 year old man suffering from life‐threating acute pulmonary embolism 52 . Due to a history of upper gastrointestinal bleeding and a poor pre‐morbid status, medical, invasive, and surgical treatments were unfavorable.…”
Section: Levosimendan In Phmentioning
confidence: 99%
“…Only very few levosimendan studies have been conducted in PH associated with lung disease and in PH related to pulmonary thromboembolism, and results are not comparable [53][54][55].…”
Section: Levosimendan In Pulmonary Hypertensionmentioning
confidence: 99%
“…Clinically available inodilators include levosimendan, milrinone, and dobutamine, all of which have different hemodynamic profiles 3 6 . Inodilators are used in acute cardiac care and in chronic pulmonary hypertension (PH), 3 , 7 but only case reports or small case series exist on their effect in acute PE 8 , 9 . At present, dobutamine has received a Class IIa recommendation limited to high‐risk PE patients, whereas neither levosimendan nor milrinone is mentioned in the European Society of Cardiology Pulmonary Embolism guidelines 1 …”
Section: Introductionmentioning
confidence: 99%